The Role of University-Ngo Cooperation in Increasing the Entrepreneurial Skills of Youth: An Evaluation Specific to Refugee Youth - Nur İncetahtacı (İzmir İktisat Dergisi)
As widely recognized, Turkey is hosting the world's highest number of registered refugees since 2011. Notably, 20% of this refugee population comprises young individuals aged 18-29, highlighting significant youth. Gaziantep, second to Istanbul in refugee concentration, accommodates over 440,000 refugees. This study delves into the necessity of forging a new symbiotic relationship between residents and migrants. Such a partnership can positively affect industry, productivity and human resource diversity. Notably, research indicates that a majority (80%) of refugees do not foresee a return to Syria, underscoring the significance of maximizing the productivity and efficiency of these individuals in their adopted regions. Consequently, the study investigates the interplay between young migrants and the city's entrepreneurship ecosystem, drawing upon data from 14 collaborative projects, focusing on enhancing local and refugee youth's capacity and entrepreneurial skills, between Gaziantep University and NGOs. The findings underscore the outcomes stemming from the alliance between young refugees and their local counterparts, which fosters innovation and productivity through collaboration. This study illuminates the potential for new ecosystems to drive entrepreneurial effectiveness and efficiency, culminating in innovation-driven accomplishments facilitated by the collaboration between refugee and local youth.